Efficacy of EDTA-NS irrigation in eradicating Staphylococcus aureus biofilm-associated infection: an in vitro and in vivo study - Junqing Lin; Jinlong Suo; Bingbo Bao; Haifeng Wei; Tao Gao; Hongyi Zhu; Xianyou Zheng (Bone & Joint Research, 2024)
Aims: To investigate the efficacy of ethylenediaminetetraacetic acid-normal saline (EDTA-NS) in dispersing biofilms and reducing bacterial infections. Methods: EDTA-NS solutions were irrigated at different durations (1, 5, 10, and 30 minutes) and concentrations (1, 2, 5, 10, and 50 mM) to disrupt Staphylococcus aureus biofilms on Matrigel-coated glass and two materials widely used in orthopaedic implants (Ti-6Al-4V and highly cross-linked polyethylene (HXLPE)). To assess the efficacy of biofilm dispersion, crystal violet staining biofilm assay and colony counting after sonification and culturing were performed. The results were further confirmed and visualized by confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). We then investigated the efficacies of EDTA-NS irrigation in vivo in rat and pig models of biofilm-associated infection. Results: When 10 mM or higher EDTA-NS concentrations were used for ten minutes, over 99% of S. aureus biofilm formed on all three types of materials was eradicated in terms of absorbance measured at 595 nm and colony-forming units (CFUs) after culturing. Consistently, SEM and CSLM scanning demonstrated that less adherence of S. aureus could be observed on all three types of materials after 10 mM EDTA-NS irrigation for ten minutes. In the rat model, compared with NS irrigation combined with rifampin (Ti-6Al-4V wire-implanted rats: 60% bacteria survived; HXLPE particle-implanted rats: 63.3% bacteria survived), EDTA-NS irrigation combined with rifampin produced the highest removal rate (Ti-6Al-4V wire-implanted rats: 3.33% bacteria survived; HXLPE particle-implanted rats: 6.67% bacteria survived). In the pig model, compared with NS irrigation combined with rifampin (Ti-6Al-4V plates: 75% bacteria survived; HXLPE bearings: 87.5% bacteria survived), we observed a similar level of biofilm disruption on Ti-6Al-4V plates (25% bacteria survived) and HXLPE bearings (37.5% bacteria survived) after EDTA-NS irrigation combined with rifampin. The in vivo study revealed that the biomass of S. aureus biofilm was significantly reduced when treated with rifampin following irrigation and debridement, as indicated by both the biofilm bacterial burden and crystal violet staining. EDTA-NS irrigation (10 mM/10 min) combined with rifampin effectively removes S. aureus biofilm-associated infections both in vitro and in vivo. Conclusion: EDTA-NS irrigation with or without antibiotics is effective in eradicating S. aureus biofilm-associated infection both ex and in vivo. Cite this article: Bone Joint Res 2024;13(1):40–51.